Bortezomib‐based therapy for relapsed/refractory multiple myeloma in real‐world medical practice. (5th September 2018) - Terpos, Evangelos; Katodritou, Eirini; de la Rubia, Javier; Hungria, Vania; Hulin, Cyrille; Roussou, Maria; Delforge, Michel; Bries, Greet; Stoppa, Anne‐Marie; Aagesen, Jesper; Sargin, Deniz; Belch, Andrew; et al.
Abstract: Objective: The efficacy and safety of bortezomib‐based therapy for relapsed/refractory multiple myeloma (RRMM) in clinical trials may differ from the oncology practice experience. The electronic VELCADE ® OBservational Study was designed to prospectively evaluate bortezomib for multiple myeloma (MM) in real‐world medical practice. Method: Patients scheduled to receive intravenous bortezomib for MM were eligible. The primary objective was to evaluate clinical outcomes, including response, time to response, time to next therapy, treatment‐free interval, progression‐free survival (PFS), and overall survival (OS). Secondary objectives included safety and healthcare resource utilization. Results: In total, 873 patients with a median of two therapy lines prior to initiating bortezomib were included. The overall response rate (≥partial response) was 69%, including 37% complete response/near‐complete response. Median time to response was 1.8 months, median time to next therapy was 9.7 months, and median treatment‐free interval was 7.9 months. After 22.6 months' median follow‐up, median PFS was 12.0 months and median OS was 36.1 months. The most common adverse events (AEs) were neuropathy not otherwise specified (19%), diarrhea NOS, and thrombocytopenia (each 17%); 230 (26%) patients discontinued bortezomib due to AEs. Of 689 (79%) patients without baseline peripheral neuropathy (PN), the rate of new‐onset any‐grade PN increased to 51% (12% grade 3/4) by cycle 8. Overall, 244 (28%) patients were hospitalized, 372 (43%) attended an outpatient visit, and 341 (39%) underwent a diagnostic/therapeutic procedure during bortezomib treatment. Conclusion: These prospective real‐world data demonstrate the effectiveness and safety of bortezomib‐based therapy for RRMM and confirm high response rates and long OS for this population.